Hubungan antara Budaya Organisasi terhadap Employee Engagement pada Karyawan BPJS Kesehatan Kantor Cabang Padang - Martiano, Robby; Dwatra, Free Dirga (Lembaga Yasin AlSys, 2024)
This research begins with the phenomenon of behavior shown by non-permanent employees of BPJS Health Padang Branch Office which leads to engagement related to the organizational culture of the company. The purpose of this research is to see how organizational culture is related to employee engagement in non-permanent employees of BPJS Health Padang Branch Office. The type used in this research is a quantitative correlational research method. The research subjects were 35 people obtained through saturated sampling techniques. The data collection tool uses an organizational culture scale consisting of 19 items with a reliability value of 0.919 and an employee engagement scale consisting of 16 items with a reliability value of 0.931. The data was processed using Karl Pearson's product moment correlation statistical technique. The research results with an rxy value of 0.814 with p=0.001 (p<0.01) show that there is a very significant positive relationship between organizational culture and employee engagement in non-permanent employees of BPJS Health Padang Branch Office. This shows that the better the organizational culture, the higher employee engagement among non-permanent employees of BPJS Health Padang Branch Office.